A SOCIEDADE DO APARTHEID EM WAITING FOR THE BARBARIANS DE J. M. COETZEE (Polifonia, 2013)
RESUMO: Neste artigo analisamos o romance Waiting for the barbarians(1980), apontando os elementos históricos e sociais retratados pelo autorcomo essenciais para a existência de um regime de exceção. Nossapesquisa foi composta por investigações históricas, sociológicas e literárias,com o objetivo de demonstrarmos como o contexto do romance éparte da sua construção, influenciando inclusive a constituição das personagens.PALAVRAS-CHAVE: África do Sul, apartheid, J. M. CoetzeeABSTRACT: This article analyses the novel Waiting for the barbarians(1980) referring to social and historical elements represented by theauthor as essentials for the existence of a regime of exception. Ourresearch involved historical, sociological and literary investigation,aiming to demonstrate how the context of the novel is part of itsconstruction, including influencing the creation of characters.KEYWORDS: South Africa, apartheid, J. M. Coetzee